2015
DOI: 10.1136/bmjopen-2014-005406
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating recovery following hip fracture: a qualitative interview study of what is important to patients

Abstract: ObjectiveTo explore what patients consider important when evaluating their recovery from hip fracture and to consider how these priorities could be used in the evaluation of the quality of hip fracture services.DesignSemistructured interviews exploring the experience of recovery from hip fracture at two time points—4 weeks and 4 months postoperative hip fixation. Two approaches to analysis: thematic analysis of data specifically related to recovery from hip fracture; summarising the participant's experience ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
136
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(153 citation statements)
references
References 25 publications
11
136
0
1
Order By: Relevance
“…Carers have important information about the patient background (i.e. health status) [50] and they suggested that their information about the patient and their family dynamic should be assessed at hospital admission [43,44]. Despite carers´ perception that they are the "glue" some of them also felt that the healthcare providers had a more educated understanding of the patient's condition; therefore they saw themselves as mainly receiving information but not providing it [44].…”
Section: Ii) Learning Through Experiencementioning
confidence: 99%
“…Carers have important information about the patient background (i.e. health status) [50] and they suggested that their information about the patient and their family dynamic should be assessed at hospital admission [43,44]. Despite carers´ perception that they are the "glue" some of them also felt that the healthcare providers had a more educated understanding of the patient's condition; therefore they saw themselves as mainly receiving information but not providing it [44].…”
Section: Ii) Learning Through Experiencementioning
confidence: 99%
“…The studies consider all types of patients, not only healthy ones (Archibald, 2003;Griffiths et al, 2015;Olsson et al, 2007;Ziden, Wenestam, Hansson-Scherman, 2008) Olsson et al (2007) described three groups of patients based on perceptions of responsibility in the rehabilitation process: 1) autonomous, self-sufficient patients who take care of themselves and search for relevant information; 2) modest, frail patients in need of more support who want information but do not ask for it; and 3) heedless, patients who are already dependent, not aware of their own responsibility and not interested in information.…”
Section: Introductionmentioning
confidence: 99%
“…Individual changes concerning the relationship with one`s own body can cause social and existential changes in relationships with others and to one`s life situation as a whole (Ziden et al, 2008). The ability to adapt to reduced mobility was considered to decline with age, but striving to regain pre-fracture mobility was important for managing personal care and day-to-day activities (Griffiths et al, 2015). Patients with hip fractures all worried about their future ability to walk again (Griffiths et al, 2015;Olsson et al, 2007;Ziden et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older, more frail patients often view their limitations as a consequence of ageing, or experience difficulties disentangling the impact of the hip fracture from the wide range of co-morbidities they experience [74]. Similar difficulties associated with the impact of multiple comorbidities have been reported in other patient populations, for example, in mental health [87].…”
Section: Discussionmentioning
confidence: 97%